Do We Have What Is Needed to Change Everything? A Survey of Finnish Software Businesses on Labour Shortage and Its Potential Impacts - Hyrynsalmi SM; Rantanen MM; Hyrynsalmi S (United States, 2022)
The fourth industrial revolution is expected to bring major changes both in society as well as in the modern industry. Naturally, it will also shake the labour market---however, not only by replacing blue collar duties by robots, but also by renewing the set of skills and competencies needed in new kinds of work duties. In this study, we use a data (n = 160) from a survey to the Finnish software businesses to evaluate how software companies perceive the labour shortage and its implications in the verge of the new industrial revolution. The results show that already now there are signs that the labour shortage might harm the growth and innovations in the ICT field. This study presents the results from the survey and discusses whether there are enough competent resources to support the industrial revolution.
This Changes Everything – ICT and Climate Change: What Can We Do? 13th IFIP TC 9 International Conference on Human Choice and Computers, HCC13 2018, Held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 19–21, 2018, Proceedings